Knot Theory and Culture: An Exploration of Alexander Polynomial in Ketupat Bata - Ja'faruddin, Ja'faruddin (Universitas Cokroaminoto Palopo, 2024)
The Ketupat bata is an intriguing geometric shape in knot theory, and this study investigates the polynomial knot that was found in the Ketupat . The objective of this study is to analyze the distinctive mathematical aspects of the diamond brick knot polynomial, which include the saturation level and intricate indexing of the polynomial. An examination of the geometric structure of the brick diamond is accomplished through the application of specialist procedures as part of the strategy that is utilized. The knot polynomial that was obtained is found to be a tetrahedral lattice. There is a mathematical relationship that can be represented by the equation Ak=-t2+5t-8+5t-1-t2 The outcome of this investigation demonstrates how essential mathematical concepts such as its geometric and structural properties.It is possible to produce a more profound comprehension of both culture and nodes by applying the notions of polynomials and nodes to the study of culture.